Chemically reacting Jeffrey fluid flow over a deformable porous layer with entropy generation analysis - Das, Utpal Jyoti (Zielona Góra: Uniwersytet Zielonogórski)
Entropy generation of a steady Jeffrey fluid flow over a deformable vertical porous layer is analysed with consideration of a first-order chemical reaction and thermal diffusion. The porous material is modelled as a homogeneous binary mixture of fluid and solid phases where each point in the binary mixture is occupied concurrently by the fluid and solid.
Keywords: deformable porous layer; Jeffrey fluid; entropy generation; Bejan number; thermal diffusion